STRATEGI KEPEMIMPINAN BKMT KABUPATEN RAJA AMPAT DALAM PENGUATAN PENDIDIKAN ISLAM DI KABUPATEN RAJA AMPAT - Bondahara, Ratna; Amin , Surahman; Abdillah, Fardan (Pascasarjana IAIN Sorong, 2023)
The aims of this research are First; To describe the leadership role of the Taklim Council Contact Agency in strengthening Islamic education in Raja Ampat Regency. Second, to describe the strategy of the Taklim Council Contact Agency in strengthening Islamic education in Raja Ampat Regency.This type of research is Qualitative Description. The research approach is a phenomenological, normative theological and sociological approach. Research data sources are primary data sources and secondary data sources. Research data collection methods use observation, interviews and documentation methods. Data processing and analysis techniques using data reduction, data presentation, comparative analysis of data and drawing conclusions.The results of this research show that the leadership role of the Taklim Council Contact Agency in strengthening Islamic education in Raja Ampat Regency is to establish good cooperative relationships, have a high work ethic, participative and responsible leadership characteristics and be trustworthy in carrying out leadership duties. The strategy of the Taklim Council Contact Agency in strengthening Islamic education in Raja Ampat Regency is to maximize the concept of education management, holding regular recitations, introducing or observing Islamic education targets and direct visits to the community (Mobile Education).